2020
DOI: 10.1002/1873-3468.13727
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of the TCP domain of PCF6 in Oryza sativa L. reveals an RHH‐like fold

Abstract: The Teosinte branched 1/Cycloidea/Proliferating cell factor (TCP) domain is an evolutionarily conserved DNA binding domain unique to the plant kingdom. To date, the functions of TCPs have been well studied, but the threedimensional structure of the TCP domain is lacking. Here, we have determined the crystal structure of the TCP domain from OsPCF6. The structure reveals that the TCP domain adopts three short b-strands followed by a helix-loop-helix structure, distinct from the canonical basic helix-loop-helix s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Until recently, these plant-specific TFs were considered similar to bHLH [52]. However, the determination of the crystallographic structure of the DBD of O. sativa PCF6 (5ZKT) revealed they rather belong to Ribbon-Helix-Helix (RHH) TFs [53], a class yet never described in plants that recognize DNA motifs in the major groove thanks to an anti-parallel beta-sheet involved in dimer formation, anchored by alpha-helices [53,54]. We have thus added the RHH class and TCP family to the “beta-Hairpin exposed by an alpha/beta-scaffold” superclass.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, these plant-specific TFs were considered similar to bHLH [52]. However, the determination of the crystallographic structure of the DBD of O. sativa PCF6 (5ZKT) revealed they rather belong to Ribbon-Helix-Helix (RHH) TFs [53], a class yet never described in plants that recognize DNA motifs in the major groove thanks to an anti-parallel beta-sheet involved in dimer formation, anchored by alpha-helices [53,54]. We have thus added the RHH class and TCP family to the “beta-Hairpin exposed by an alpha/beta-scaffold” superclass.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the TCP domain structure has remained intact ( Kosugi and Ohashi, 1997 ; Cubas et al, 1999 ). The protein structural analysis of the bHLH TFs has shown that the TCP domain is characterized by a basic residue-rich region forming a typical fold of 3 short β -strands (β1, β2, and β3) and two consecutive α-helices (α-1 and α-2) ( Sun et al, 2020 ). However, the TCP domain is different to the bHLH domain ( Carrara and Dornelas, 2021 ).…”
Section: Tcp Conserved Domainsmentioning
confidence: 99%
“…Interestingly, their analysis in rice OsPCF6 protein, disclosed that the TCP domain dimerize with other two TCP domains, each forming a stable conformation that adopts the ribbon-helix-helix (RHH) fold rather than the bHLH motif previously predicted. Implying that the TCP protein can also be classified into the RHH family ( Liu et al, 2019 ; Sun et al, 2020 ). Although these findings are not conclusive, the homology modelling of TCP protein has also demonstrated their ability to form homodimers and/or heterodimers with other TCP proteins to bind DNA ( Parapunova et al, 2014 ).…”
Section: Tcp Conserved Domainsmentioning
confidence: 99%
“…In 2010, a model of the TCP domain bound to a B-form dsDNA with the sequence GTGGTCCC was reported using a DNA-bound MyoD structure as a template ( 9 ); nevertheless, this structural model has been misleading. Recently, the apo structure of the TCP domain from OsPCF6 was solved, and the TCP domain was demonstrated to possess a low-homology bacterial RHH fold by structural comparison ( 26 ). The HLH region of the TCP domain does resemble the bacterial RHH domain, but the basic regions of the two folds are quite distinct.…”
Section: Introductionmentioning
confidence: 99%